THE INFLUENCE OF INITIAL CROSSBREEDING COMPONENTS ON THE FORMATION OF SELECTION-VALUABLE TRAITS IN POTATO HYBRID OFFSPRING - Zaviriukha П. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
А number of crossings of potato varieties Zakhidna, Volia, Lishchyna of the Lviv NEU selection and foreign varieties Nevska, Krasa were carried out, both with one another and with promising hybrids. As a result, F1 hybrid seeds of 19 combinations of crosses were obtained. Potato seedlings of the first year were grown from the obtained F1 hybrid seeds in 2020-2021. In the seedling nursery, 19 hybrid populations were evaluated and the best forms were selected. Thus, the largest number of selectively valuable forms was selected from the combination of Hybrid 99/9-13 × Zakhidna – 12 pcs. At the same time, productivity limits ranged from 683 to 2028 g/bush with a fairly high population average of 1152 g/bush for the selected forms. In the selection of potatoes for increased and high starchiness of the tubers, the crossbreeding of Hybrid 02/12-18 × Zakhidna is promising. The starch content in tubers of the selected seedlings of this hybrid population reached 20.5 %, compared to the average value of 16.4 %. An increased content of starch in the tubers (19.5 %) was also noted in the selected F1 seedlings of the crossing combination of Hybrid 99/9-13 × Zakhidna. The conducted research established that the Volia variety is a good producer of highly productive offspring due to its use in crossings of both maternal and paternal forms. In particular, the progeny of the Volia × Hybrid 00/11-3 population had the highest productivity: the maximum weight of the trait reached 2286 g/bush, compared to the population average of 1460 g/bush for 8 selected forms. It is noteworthy that the selected F1 hybrid seedlings of this population combined high productivity with the increased and high starch content in the tubers and their sufficient size. In particular, the limits of starch content of tubers varied between 14.9–20.5 % with an average value of 17.0 %, and the average weight of one tuber was 73–225 g with an average value of 123 g. Hybrid combinations are also promising in the selection of potatoes for starch content of the Hybrid 00/20-4 × Volia and Volia × Hybrid 02/10-6 – the average starch content in the tubers of the selected seedlings of these crossing combinations was 16.0 and 17.6 % respectively. For the use of Lishchyna variety as a mother form in crossings, the hybrid combination of Lishchyna × Hybrid 02/9-10 is the most qualitative. At the same time, the productivity of the selected hybrid seedlings (16 pieces) ranged from 517 to 2000 g/bush with an average value of 1000 g/bush, the starch content was 10.0–20.5 %, the average was 17.1 %, and the weight of one tuber - from 45 to 160 g, with an average weight of 88 g. It has been established that by involving in the crossing of early-ripening foreign potato varieties Krasa (Czech Republic) and Nevska (Russian Federation) it is possible to obtain high-quality hybrid potato seedlings F1, especially when the indicated varieties are pollinated with Hybrid 00/35-7. Thus, 10 hybrids were selected from the Nevska × H.00/35-7 hybrid combination, the productivity limits of which ranged from 875 to 1822 g/bush with a high average value of 1235 g/bush. At the same time, the variability of the starch content was in the range of 11.4–16.4 % with an average value of 14.2 %. Some of the selected seedlings of this combination were distinguished by high tuber size - the weight of one tuber was up to 160 g. In the crossing combination of Krasa × H.00/35-7, the frequency of selection of selection-valuable forms was slightly higher than in the previous hybrid combination and amounted to 17 hybrid seedlings. At the same time, the productivity of individual selected forms reached 1800 g/bush, the starch content was 20.1 %, the average weight of one tuber was 138 g, and their number under the bush was up to 22 pieces. In the process of applied selection work with potatoes, the selection value of 17 hybrid populations obtained with the participation of the varieties of the Lviv NEU Zakhidna, Volia, Lyshchyna, foreign varieties Nevska, Krasa and hybrids of complex intervarietal origin as hybridization components was established. The influence of the initial components of crossing on the formation of selection-valuable traits in potato hybrid offspring and the frequency of selection of selection-valuable forms has been established. The selection of the best F1 hybrid potato seedlings (141 pcs.) with high parameters of selection-valuable traits, which constitute high-quality raw material for further selection work, was carried out.